Educational Training for Students' Self-Efficacy in Learning Science and Mathematics - Fatmi, Nuraini; Muhammad, Iryana; Setiawaty, Sri (Universitas Gajah Putih, Indonesia, 2023)
This service is carried out by MTsS Safinatussalamah Al-Munawarah, Lhokseumawe City. The priority issue of partners (Safinatussalamah Al-Munawarah) is in terms of learning. In this case, in partner schools, students have not fully self-efficacy in learning mathematics and science. This is due to the lack of motivation in the form of educating students on the importance of self-efficacy abilities. The purpose of implementing the activities in this lecturer service program can be detailed as follows: a) To provide education to all students on the importance of having self-efficacy skills, especially in learning mathematics and science. b) Provide opportunities for all students to be able to explore the potential that exists within students. c) Train and improve students' caring attitudes, empathy for educational conditions, and provide practical scientific services and environmental knowledge assistance. The implementation method is a field survey and training method by determining partner problems, based on the results of a situation analysis on partners that has been carried out through a preliminary survey. The results of the service stated that students began to have a sense of independence in managing themselves after understanding the concept of self-efficacy. This is indicated by the acquisition of the highest percentage of the questionnaire score of 0.52. Or by 52% and in the very high category.